Tomografia por coerência ótica: implementação e aplicações em fibras óticas - Saccon, Fernando Antonio Moura (2010)
Optical coherence tomography is a high-resolution and non invasive technique that allows constructing three-dimensional images in real time and in vivo, with applications mainly in medicine. However, industrial applications of the OCT are promising although underexploited. This work presents a time domain optical coherence tomography system to characterize photorefractive devices in optical fibers. These devices are produced by the Grupo de Dispositivos Fotônicos e Aplicações at UTFPR for applications in the sensing area. The characterization of such devices is an important issue to improve the production process. The main advantage of OCT is the possibility to obtain high- resolution images and analyze qualitative and quantitatively parameters like refractive index and the modulation period of devices. We developed the mechanical parts of the system and the software for control and acquisition data in LabVIEW language. The software commands motors movements and collect data of the acquisition system. The results demonstrate the viability of the built system, enabling the visualization of the long period grating recorded with electric arc. Refractive index measurements of crystals were done, which obtained values are in good agreement with literature. Due the high sensitivity of the system it is possible to identify interfaces of a multimode optical fiber (in this case the core diameter is bigger than the system resolution) and the various interfaces – core, cladding, coating – are shown in the interferograma, allowing quantify the refractive indexes when the diameter is previously known.